3D printed noise-cancelling triboelectric nanogenerator - Lee, Jin Pyo; Ye, Byeong Uk; Kim, Kyeong Nam; Lee, Jae Won; Choi, Won Jun; Baik, Jeong Min (ELSEVIER SCIENCE BV, 2017)
Triboelectric nanogenerator (TENG), which converts the ambient mechanical energy to electricity by friction, is one of the most promising methods for powering up portable devices. Despite of the successful development so far, there still remain some issues to be improved. Here, we focus on the generation and maintenance of high output-power under harsh environments, and the noise cancellation of the device to keep a stable operation for a long period of time. The TENG, fabricated using a 3D printer, is a fully-packaged, cylinder-shaped device with polydimethylsiloxane (PDMS) bumpy balls inside and linearly patterned Al film on the inner surface. The new design and optimization remarkably increases the output power up to 45 mW, operable under harsh environments such as water, providing enough DC power for charging a battery of smart watch. The noise occurring during the operation is canceled to the noise level (similar to 50 dB) of a normal conversation, by approximately 20 dB, with no degradation of the output power by using highly compressible, conductive Ag nanowires-embedded polyurethane sponge instead of Al. This helps people around the device feel comfortable during the operation. Finally, as a large-scale power supply, windmill composed of three TENGs, are also developed.
Keywords: WATER-WAVE ENERGY; HARVESTING ENERGY; CONTACT; VIBRATION; GENERATOR; PRESSURE; SYSTEM; IMPACT; MODE